PENATAAN BERKAS DI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN SLEMAN - , M ICHLASUL KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This last assignment report is discuss about the file structure on Dinas Kebudayaan dan Pariwisara Kabupaten Sleman that has more focused on Dynamic Archive letter. Structuring file is an activity to order and organize file in a systematic draft with perceive the function, shape, and characteristics of the file that on purpose to support quicken organization accomplishment. The method of data collection enclosed observation and participation is the collect techniques with make an direct observation to the office, interview is the collect techniques that conduct with make an interview with the informant directly, and the literature studies of the data collection is from so many literature to strengthen the arguments and get the relevant supporting data. Summary of this report is the file structure on Dinas Kebudayaan dan Pariwisata is fit with the archival standard. File structure that fit to the archival standard is make it easier to re-find it. The problem that occurs is, archives are not directly stored so often happens buildup. Constrains that often happens is, after the archive is stored so that the note does not directly lead to the accumulation of archives and will have difficulty in reinvention.